Heterogeneity of Thyroid Function and Impact of Peripheral Thyroxine Deiodination in Centenarians and Semi-Supercentenarians: Association With Functional Status and Mortality. (25th August 2018) - Ostan, Rita; Monti, Daniela; Mari, Daniela; Arosio, Beatrice; Gentilini, Davide; Ferri, Evelyn; Passarino, Giuseppe; De Rango, Francesco; D'Aquila, Patrizia; Mariotti, Stefano; Pasquali, Renato; Fanelli, Flaminia; et al.
Abstract: Thyroid hormones (FT3, FT4) and thyroid-stimulating hormone (TSH) were evaluated in a population of 672 well-characterized Italian subjects (age range: 52–113 years), including an unprecedented number of centenarians, semi-supercentenarians, as well as centenarian's offspring and age-matched elderly (CENT, 105+, CENTOFF, and CTRL, respectively). The results show that FT3 level and FT3/FT4 ratio decrease while FT4 and TSH increase in an age-dependent manner. In CENT/105+, higher FT4 level, and lower FT3/FT4 ratio are associated with an impaired functional status and an increased mortality. A cluster analysis identified three clusters of CENT/105+ based on their FT3, FT4, and TSH levels. Cluster 3, characterized by lower FT3 and TSH and higher FT4, shows the worst health status and the shortest survival. Thus, the age-related changes of thyroid hormones extend to the most advanced age, and CENT/105+ are highly heterogeneous regarding thyroid function. This heterogeneity is related to different health, functional and cognitive status, as well as with survival/mortality in CENT/105+. Finally, we investigated a remarkable number of CENT/105+ showing a thyroid profile suggestive of non-thyroidal illness syndrome (NTIS) (excluded from the previous analysis). NTIS CENT/105+ are characterized by a worse functional and cognitive status and an increased mortality with respect to CENT/105+ without NTIS.